An Unexpected Etiology of Myocardial Ischemia in Young - Bouomrani, Salem; Souissi, Oussema; Guermazi, Mouna; Yahyaoui, Souad; Trabelsi, Safa (Journal of Hypertension and Cardiology, 2019)
Introduction The cardiac localization of hydatid cyst (HC) is rare and little known. It is exceptionally primary and isolated. Myocardial ischemia remains an exceptional and unusual manifestation of this localization. We report the original observation of cardiac HC revealed by acute myocardial ischemia in a young subject. Observation A 35-year-old patient with no notable pathological history was admitted to our department via the emergency room for acute anterior chest pain. The somatic examination was without abnormalities as well as the baseline biological tests. The electrocardiogram demonstrated epicardial ischemia in the infero-lateral territory without other abnormalities. The cardiac troponin I was slightly elevated (32ng/l, N<19ng/l). Subsequent controls after 30min, 60min and 180min did not show significant variations. Subsequent investigations (CT, coro-CT, coronary angiography) led to the diagnosis of intramyocardial HC of the left ventricle, with no abnormalities of the coronary arteries. After surgical excision, the evolution was favorable with normalization of the electrocardiogram and the troponin Ic. Conclusion Cardiac localization of this parasitosis is exceptional and characterized by an important clinical polymorphism making its diagnosis a real challenge. It seems useful to discuss the diagnosis of cardiac HC in front of any unexplained electrocardiogram abnormality occurring in endemic zone.
Keywords: Hydatid cyst; heart; echinococcosis; parasitosis; myocardial ischemia.